KARAKTERISTIK ENTREPRENEUR MELALUI MULTIPLE DISKRIMINAN ANALISIS (Studi Pada Etnis Tionghoa, Jawa dan Minang di Bekasi Utara) - Handaru, Agung Wahyu; Pagita, Magdalena Prita; Parimita, Widya (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2015)
KARAKTERISTIK ENTREPRENEUR MELALUI MULTIPLEDISKRIMINAN ANALISIS(Studi Pada Etnis Tionghoa, Jawa dan Minang di Bekasi Utara)Agung Wahyu HandaruFakultas Ekonomi Universitas Negeri JakartaEmail: agung_1178@yahoo.comMagdalena Prita PagitaFakultas Ekonomi Universitas Negeri JakartaEmail: magdalenapritapagita@gmail.comWidya ParimitaFakultas Ekonomi Universitas Negeri JakartaEmail: widya_parimita@yahoo.comABSTRACTThe purpose of this study is : 1) To find a description about demographic ofChinese ethnic, Javanese ethnic and Minang ethnic. 2) To discriminant testbetween Chinese ethnic and Javanese ethnic. 3) To discriminant test betweenChinese ethnic and Minang ethnic. 4) To discriminant test between Javaneseethnic and Minang ethnic. 5) To discriminant test between Chinese, Javanese andMinang ethnic. The analysis conducted in this research is descriptive anddiscriminant analysis. The study was conducted of 60 entrepreneurs in BekasiUtara especially in 2 area that is Wisma Asri and Pondok Ungu Permai usingconvenience sampling method. While the techniques of data collection is done bydistributing questionnaires, which are then processed using SPSS 21. The resultsshows that 1) Entrepreneur dominated by men with less than 30 years old withhigh school education level, have 10 years business with its own capital resourcesthat is less than 50 million and a gross monthly income of less than 10 million.2)The variable characteristics entrepreneurs who make different ethnic Chineseand Javanese is Tuna Satak Bathi Sanak with strength classification accuracy. 3)The variable characteristics entrepreneurs who make different ethnic Chinese andMinang is Hongsui with strength classification accuracy. 4) The variablecharacteristics entrepreneurs who make different ethnic Javanese and Minang arePanggautan Gelaring Pambudi and Tuna Satak Bathi Sanak with strengthclassification accuracy. 5) The variable characteristics entrepreneurs who makedifferent ethnic Chinese, Javanese and Minang are Hopeng and Tuna Satak BathiSanak with strength classification accuracy.Keywords : Characteristicsof Entrepreneurs, Discriminant Analysis.